Nigeria : Country Procurement Assessment Report, Volume 1. Summary of Findings and Recommendations - World Bank (Washington, DC, 2013)
This Country Procurement Assessment Report (CPAR) for Nigeria reviews the procurement system in terms of: legal framework, public sector procurement of goods/works/consultants, procurement performance in Bank-financed projects, private sector procurement, trade practices, financial framework, and electronic commerce. The report consists of two volumes. The first volume contains a summary of findings and recommendations and an Action Plan for implementing the recommendations. The second volume contains the main text and supporting. The report recommends: a) the enactment of a procurement law to underpin the reforms being proposed; b) the establishment of a Public Procurement Commission to be vested with oversight responsibilities for public procurement; c) the revision of key areas of the Financial Regulations to make them more transparent; d) a complete restructuring of the tender boards and approval procedures for contracts; and e) building procurement capacity in the public sector through restoration of professionalism in procurement and intensive training of procurement staff.